Pelatihan Mengalihwahanakan Karya Sastra Menjadi Teks Iklan untuk Guru Bahasa Indonesia SMA Kabupaten Rembang - Mukh Doyin; Zuliyanti Zuliyanti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
In the Independent Curriculum implemented in schools starting the 2024/2025 academic year, there are Learning Outcomes (CP) that read "Students are able to modify/deconstruct literary works for creative economic purposes" and "Students are able to translate one text into another for creative economic purposes". In reality, in schools, there are still few teachers who connect literary works with economic issues, many teachers are still unfamiliar with the concept of translation, not many teachers have participated in translation training, and there is no guidebook for translating literary texts into non-literary texts or vice versa. This also applies to high school Indonesian Language teachers in Rembang Regency. Combining these two Learning Outcomes and connecting them to conditions in society, this community service conducted training on translating literary works into advertising texts for high school Indonesian Language teachers in Rembang Regency. The training was carried out with the first stage providing material on translation and advertising and the second stage providing mentoring to teachers to practice translating literary works into advertising.